2001
DOI: 10.1054/bjoc.2000.1684
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-amplified kinase BTAK is amplified and overexpressed in gastric cancers with possible involvement in aneuploid formation

Abstract: Summary Our recent analysis of gastric cancers using comparative genomic hybridization (CGH) revealed a novel high frequent copy number increase in the long arm of chromosome 20. Tumour-amplified kinase BTAK was recently cloned from breast cancers and mapped on 20q13 as a target gene for this amplification in human breast cancers. In the study presented here, we analysed BTAK copy-number and expression, and their relation to the ploidy pattern in 72 primary gastric cancers. Furthermore, wild-type BTAK and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(133 citation statements)
references
References 29 publications
2
128
1
2
Order By: Relevance
“…52 Amplification and overexpression of the BTAK gene, which encodes breast tumor-amplified kinase (identical to aurora2, ARK1 and STK15), have been reported in primary gastric adenocarcinomas that were associated with aneuploidy and poor prognosis. 47 Moreover, amplification and overexpression of the AIB1 (amplified in breast cancer 1) gene, a member of the steroid receptor coactivator family, appears to be useful as a marker of poor prognosis in gastric cancer. 49 Recently, it was reported that TOP1, TFAP2C and NCOA3 (AIB1) might be prognostic indicators in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…52 Amplification and overexpression of the BTAK gene, which encodes breast tumor-amplified kinase (identical to aurora2, ARK1 and STK15), have been reported in primary gastric adenocarcinomas that were associated with aneuploidy and poor prognosis. 47 Moreover, amplification and overexpression of the AIB1 (amplified in breast cancer 1) gene, a member of the steroid receptor coactivator family, appears to be useful as a marker of poor prognosis in gastric cancer. 49 Recently, it was reported that TOP1, TFAP2C and NCOA3 (AIB1) might be prognostic indicators in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Aurora-A is overexpressed in many cancer types and mapped to chromosome 20q13 region, which is frequently amplified in many human cancers (Tanaka et al, 1999;Gritsko et al, 2003;Li et al, 2003). Overexpression of Aurora-A significantly correlates with the induction of aneuploidy, centrosome anomaly, poor prognosis and invasiveness of the primary human tumors and of experimental tumors in animal model systems (Sakakura et al, 2001;Buschhorn et al, 2005). Aurora-A levels and functions are regulated by multiple mechanisms such as gene amplification, transcription, post-translational modifications including phosphorylation/dephosphorylation and proteolysis through proteasome-dependent pathway (Honda et al, 2000;Walter et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Ectopic expression of Aurora-A in mouse NIH3T3 cells display the phenotype of abnormal centrosomes replication and cell transformation. Moreover, it has been shown that over-expression of Aurora-A in diploid human breast epithelial cells causes aberrant centrosome replication, as well as induction of aneuploidy, indicating that there are intrinsic links between aberrant regulation of Aurora-A activity and pathogeneses of aneuploidy and chromosomal instability [70,71]. Recently, Meraldi et al show that over-expression of Aurora-A gave rise to centrosome amplification and polyploid [72].…”
Section: Aurora and Cancermentioning
confidence: 99%